Planning and Designing Effective Metrics - Klubeck, Martin (Springer eBooks, 2015)
Metrics are a hot topic. Executive leadership, boards of directors, management, and customers are all asking for data-based decisions. As a result, many managers, professionals, and change agents are asked to develop metrics, but have no clear idea of how to produce meaningful ones. Wouldn't it be great to have a fast, simple explanation of how to plan for and then design measurements to improve your organization? Planning and Designing Effective Metrics-an abridged version of author and metrics expert Martin Klubeck's Metrics: How to Improve Key Business Results-provides that explanation and the tools you'll need to make your organization more effective. Not only does this brief book explain the "why" of metrics, but it walks you through a step-by-step process to create a clear picture of organizational health and how well you satisfy customer needs. This book: Provides a guide for planning and designing useful metrics based on your unique organizational needs Offers the theory behind metrics to help you get exponentially better practical results Shows how to select and use the proper tools for creating, implementing, and using metrics Provides examples of how to identify, collect, analyze, and report metrics that will be immediately useful for improving all aspects of the enterprise Planning and Designing Effective Metrics will help you to measure the right things, the right way-the first time. No wasted effort, no chasing data. You will learn how to create valuable measures of organizational success, like repeat customers, customer loyalty, and word-of-mouth advertising. That will help you not only to improve organizational results-you'll also multiply your career opportunities.